2022
DOI: 10.1002/mde.3796
|View full text |Cite
|
Sign up to set email alerts
|

Does environmental regulation affect firms' ESG performance? Evidence from China

Abstract: Taking the advantage of the revise "Environmental Protection Law" implemented in China as an exogenous shock event, we evaluate the impact of environmental regulation on firms' ESG performance by the difference-in-difference approach. We find that this policy improves state-owned firms' ESG performance. Additionally, our results demonstrate that better ESG performance encourages firms' stock liquidity, and the stock liquidity of state-owned firms with high ESG performance is stronger than that of private firms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Regional environmental pollution aggravates the operational uncertainty of enterprises, forcing enterprises to make strategic adjustments and increase green investment, thus significantly improving ESG performance in the next period, which is more significant when the environmental regulatory pressure is greater and the market attention is higher (Yukun and Mengmeng, 2023). Taking the revision of China’s Environmental Protection Law as an exogenous impact event, it is found that environmental protection policies can significantly improve ESG performance of Chinese state-owned enterprises (Lu and Cheng, 2023). ESG performance is also strongly related to management tenure, with an increase in management tenure decreasing the quality of ESG disclosure, and an increase in median ESG disclosure scores of about 9.7% in two years after a CEO change (McBrayer, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Regional environmental pollution aggravates the operational uncertainty of enterprises, forcing enterprises to make strategic adjustments and increase green investment, thus significantly improving ESG performance in the next period, which is more significant when the environmental regulatory pressure is greater and the market attention is higher (Yukun and Mengmeng, 2023). Taking the revision of China’s Environmental Protection Law as an exogenous impact event, it is found that environmental protection policies can significantly improve ESG performance of Chinese state-owned enterprises (Lu and Cheng, 2023). ESG performance is also strongly related to management tenure, with an increase in management tenure decreasing the quality of ESG disclosure, and an increase in median ESG disclosure scores of about 9.7% in two years after a CEO change (McBrayer, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Enterprise ESG, as an important indicator for measuring sustainable development of enterprises, represents the level of sustainable development concepts practiced by enterprises in environmental, social and corporate governance (Munoz-Torres et al , 2019), which has a significant impact on green and sustainable development of the economy and society. To explore how to effectively improve ESG performance of enterprises, scholars have conducted in-depth studies on traditional factors such as national policies (Lu and Cheng, 2023), enterprise scale, enterprise strategy (Rajesh et al , 2022) and R&D investment (Liang and Li, 2023). However, there are generally few studies on how digital factors such as enterprise digital transformation affect enterprise ESG performance (Mu et al , 2023; Hu et al , 2023), and most of them are in the initial stage.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang finds that high government subsidies will encourage enterprises to increase investment in R&D and promote digital transformation, which will ultimately improve ESG performance [ 30 ]. Moreover, the pressure of strong environmental regulation will encourage enterprises to adjust their green development strategies and actively improve their ESG performance, which is conducive to increasing the enterprises' stocks liquidity and promoting their sustainable development [ 31 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a critical indicator, ESG is commonly applied to evaluate enterprises’ sustainable development capacity. Therefore, scholars have dedicated considerable research to explore the potential determinants of ESG by examining the performance of enterprise (Lins et al, 2017; Giuli and Kostovetsky, 2014) [ 1 , 2 ], green finance (Xu et al, 2023; Zhang, 2023a; Xue et al, 2023) [ 3 5 ], corporate leadership (Dabbebi et al, 2022; Burke, 2021; Liu and Zhang, 2023; Ritz, 2022) [ 6 9 ], ownership (Rees and Rodionova, 2015; Nofsinger et al, 2019; Weber, 2014) [ 10 12 ], and environmental regulation (Chen et al, 2022; Yan et al, 2022; He et al, 2023; Shu and Tan, 2023; Lu and Cheng, 2023) [ 13 17 ]. Nonetheless, there is a lack of discussion remains regarding the relationship between the NIGCG and environmentally friendly enterprises’ ESG.…”
Section: Introductionmentioning
confidence: 99%